The global information society - Currie, Wendy. (John Wiley and Sons, 2000)
The emerging global information society (GIS). Internet commerce. Defining a legal and regulatory framework for Internet commerce. Market as opportunity. Gaining competitive advantage from business-to-consumer internet commerce...